QoS protection optimisation for MPLS. (6th June 2011) - Rizk, Rawya; Elmaghraby, Alyaa; Marie, Mahmoud
Path protection is an important aspect to realise uninterrupted transmission in case of failure MPLS-based networks. In this paper, it is shown that none of the existing protection backup path methods is optimal at all protection parameters and network constraints. Hence, a general QoS backup protection optimisation policy applicable to a wide range of network situations and traffic types is proposed. A comparison between the proposed policy and the conventional protection backup methods is performed. The numerical results show a significant improvement of the proposed QoS protection over conventional protection backup methods at variable protection parameters, network constraints and traffic types.